Dealing with the Records of Closing Hospitals: The Calgary Area Health Authority Plan - Denham, Elizabeth (Archivaria, 1996)
The reorganization of Alberta’s health care system and the establishment of regional authorities necessitates the management of current and historical records of individual institutions. In particular, institutions which are closing or whose functions are being amalgamated with others require identification and preservation of their archival records and cultural artifacts. In Calgary in 1996, three major acute care hospitals were closed; two of these institutions were over one hundred years old. The archivist can play a vital role during the closure of health care centres, managing the records appraisal and disposition process, as well as advising in the more human side of such closures. Archivists can assist health care authorities with the management of legacy issues which arise during the closure of community institutions. RÉSUMÉ Les réorganisations du régime des soins de santé de l’Alberta et l’institution de services de santé régionaux commandent une gestion des documents actifs et historiques d’institutions individuelles. Plus particulièrement, les institutions en voie de fermeture ou celles dont leurs fonctions sont fusionnées avec d’autres, doivent être identifiées et leurs documents archivistiques et artefacts culturels, conservés. À Calgary en 1996, trois importants hôpitaux de premiers soins fermèrent leurs portes; deux de ces institutions étaient plus que centenaires. L’archiviste peut jouer un rôle de premier plan lors de la fermeture de ces services de santé, en gérant l’évaluation et la disposition des dossiers tout en faisant des recommandations tenant compte des personnes. Les archivistes peuvent également prêter leurs concours aux services de santé régionaux en gérant les questions d’ordre légal que ne manquent pas de susciter pareilles fermetures.